Palina DEVELOPMENT OF COHERENT SPEECH INNOVATIVE METHODS IN TEACHING ENGLISH: DEVELOPMENT OF COHERENT SPEECH INNOVATIVE METHODS IN TEACHING ENGLISH - Botirova, Palina (Журнал иностранных языков и лингвистики, 2022)
As a teacher, we all concern about the growth of their imaginative ability, thought, reasoning, and often they neglect such an equally important detail as the development of coherent speech. Many teachers proceed from the consideration that students, when observing them, can independently learn to articulate their thoughts coherently. That is not the case; the learner needs to be encouraged to create rational relations with his own voice. There are a lot of activities that we describe in this article to do this.